Analysis of Key Factors of Cost Overrun in Construction Projects Based on Structural Equation Modeling - Sizi Dong; Mukhtar Ahmed; Vuttichai Chatpattananan (Sustainability, 2025)
Cost overruns are prevalent in global construction industries, propelled by the swift expansion of the construction sector. To tackle this difficulty, it is essential to comprehend the primary elements leading to these overruns. This research examines the correlation between systematic elements affecting construction costs via a literature review, expert interviews, exploratory factor analysis (EFA), and structural equation modeling (SEM). A theoretical framework analyzes contract management, resource distribution, and external environmental factors affecting cost overruns. Twenty-four criteria were selected via literature review and expert consultation, and data from 212 questionnaires were analyzed. The results identify 22 critical elements classified into project management, resources, supply chain, and external and environmental influences. Project management and resources, together with supply chain, exerted the most significant influence. SEM study indicates that management inadequacies intensify resource problems, whereas proficient internal management alleviates external difficulties. This research offers practical recommendations for mitigating budget excesses and enhancing project cost-effectiveness.
Keywords: Construction Project Management and Performance; BIM and Construction Integration